Hyperbaric oxygen treatment for Parkinson's disease with severe depression and anxiety: A case report. Issue 9 (March 2018) - Xu, Jin-Jin; Yang, Si-Tong; Sha, Ying; Ge, Yuan-Yuan; Wang, Jian-Meng
Abstract: Rationale: Patients with Parkinson's disease (PD) frequently suffer from psychiatric disorders, and treating these symptom whereas managing the motor symptoms associated with PD can be a therapeutic challenge. Patient concerns: We report a case of PD patient with severe depression and anxiety that refused to be treated with dopaminagonists or SSRIs, the most common treatments for PD patients suffering from psychiatric symptoms. Diagnoses: Parkinson's disease with severe depression and anxiety. Interventions: This man was treated with hyperbaric oxygen treatment for 30 days. Outcomes: Clinical assessment scores for depression and anxiety, including Unified Parkinson's Disease Rating ScaleI (UPDRS I), UPDRS II, Hanmilton Depression Rating Scale, and Hamiliton Anxiety Rating Scale, were improved following the hyperbaric oxygen treatment. Lessons: Hyperbaric oxygen treatment may be a potential therapeutic method for PD patient suffering from depression and anxiety. Further research is needed to validate this finding and explore a potential mechanism.